Pengaruh Kepemimpinan Tranformasional, Budaya Organisasi, Lingkungan dan Stress Kerja terhadap Rework di Mediasi Oleh Work Motivation pada Pelaksanaan Proyek Konstruksi - Turrahmi, Kurnia; Widyastuti, Umi; Sariwulan, Tuty; Yohana, Corry (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
During the implementation period as well as during the maintenance period, there was a lot of work improvement, demolition, or in other words there was a lot of rework, where this rework illustrates the poor quality performance of the project implementation. Many aspects at the implementation stage of this construction project can cause product quality failure (non-performance) so that it must be disassembled and reworked, one of these factors is caused by the aspect of human resources. Quality performance problems that lead to rework can be said to often occur in the implementation of construction projects, both in the type of road projects, bridges, buildings, waterworks, and other types of construction projects. Rework causes cost overruns in project implementation which impact on project cost performance, and ultimately affect overall company performance. One of the dominant causes of the rework incident, among other aspects, is human resources. This research uses descriptive research method. The role of human resources is essentially one of capital and holds the most important position in achieving company goals. To achieve the success of a company not only in terms of technological excellence, but the role of human resources is the most important component in achieving company success.